2000
DOI: 10.1016/s0022-5347(05)67706-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Intravesical Bacillus Calmette-Guerin Are Not Affected by Substaging of High Grade T1 Transitional Cell Carcinoma

Abstract: Substaging of T1 tumors did not affect response to BCG in regard to recurrence or progression. Therefore, intravesical BCG is effective for stages T1a and T1b disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 17 publications
1
36
0
5
Order By: Relevance
“…Platz et al 35 identified muscularis mucosae in only 33% of their cases and found no significant prognostic value in substaging pT1 cancer using this criterion. With median followup of 71 months, Kondylis et al 43 found no difference in recurrence and progression rates between patients with T1a and T1b cancer using muscularis mucosae invasion for substaging. Cancer progression rates were 78 and 71% for T1a and T1b cancer, respectively.…”
Section: Substaging Of Pt1 Bladder Carcinomamentioning
confidence: 99%
“…Platz et al 35 identified muscularis mucosae in only 33% of their cases and found no significant prognostic value in substaging pT1 cancer using this criterion. With median followup of 71 months, Kondylis et al 43 found no difference in recurrence and progression rates between patients with T1a and T1b cancer using muscularis mucosae invasion for substaging. Cancer progression rates were 78 and 71% for T1a and T1b cancer, respectively.…”
Section: Substaging Of Pt1 Bladder Carcinomamentioning
confidence: 99%
“…Kondylis et al [29] reported that tumor multi-focality and associated CIS were associated with increased risk of progression. Substaging lesions based on the presence or absence of muscularis mucosae invasion in a series of 49 patients did not improve prediction of recurrence (69 vs. 65%) or progression (22 vs. 29%) after BCG therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports in the past 10 years have demonstrated a worse prognosis for T1 tumors with deep lamina propria invasion, with progression rates ranging from 29% to 55% [20][21][22]. Subgrouping of T1 tumors uses the muscularis mucosa as a landmark of microstaging.…”
Section: T1 Substagingmentioning
confidence: 99%
“…bladder cancer, Kondylis et al showed that substaging of T1 tumors did not affect response to BCG regarding recurrence or progression [20]. In contrast, Orsola et al reported that patients with high-grade T1 bladder cancer invading the muscularis mucosa (T1b) had a seven times higher risk of a positive repeat TUR at 3 months after the initial TUR and BCG therapy if the initial tumor was greater than 3 cm and a five-fold increased risk if associated with CIS [21,22].…”
Section: T1 Substagingmentioning
confidence: 99%